Coronary Artery Disease in Diabetes Patients: Prevention and Management - Salman, Mohammad; Rahman, Mohammad Ferdous Ur; Siddique, Khawer Naveed; Khan, Md Mizanur Rahman; Anwar, Mohammed Shahed; Ahmed, Md Khurshed; Sultan, Md Ashraf Uddin; Rahman, Md Atiqur (University Heart Journal, 2010)
Diabetes mellitus (DM) increases the risk of cardiovascular events in patients with cardiovascular disease as well as in patients without any previous history of ischemic heart disease (IHD). This inordinate increase in the risk of coronary events in diabetic patients is attributed to multiple factors, including glycation and oxidation of proteins and increased prevalence of classic risk factors of coronary disease, such as hypertension, obesity, and dyslipidemia. Despite advances in the management of cardiovascular disease, a large proportion of diabetic subjects continue to have uncontrolled hyperglycemia, hypertension, and dyslipidemia. Patients with CAD and pre-diabetic states should undergo lifestyle modifications aimed at preventing DM. In patients with CAD and DM, routine use of aspirin and an angiotensin-converting en zyme inhibitor (ACE I) - unless contraindicated or not tolerated - and strict glycemic, blood pressure, and lipid control are strongly suggested. The results after revascularization in diabetic patients are usually worse compared with non-diabetic patients. Advances in PCI include the use of drug-eluting stents and adjunctive drug therapies, such as GpIIbIIIa antagonists. Glycemic control is an important determinant of outcome after revascularization in diabetic patients. In this review, some of these landmark studies are reviewed and some practical guidelines of management are suggested. Key words: Angiotensin-converting enzyme inhibitor; Coronary artery disease; diabetes mellitus; dyslipidemia. DOI: 10.3329/uhj.v5i2.4559 University Heart Journal Vol.5(2) July 2009 pp.75-78